Novas tecnologias e profissão pedagógica: análise das melhores práticas (no exemplo de um grupo de universidades). - Ковтун, Альбіна; Mikheieva, Oksana; Otroshko, Tamara; Sydorenko, Tetiana; Sviderska, Oksana (My University, 2021)
The purpose of the study is the analysis of best practices in the implementation of new technologies in the system of university education and their impact on the development of the teaching profession. Research tasks: - to conduct a sociological survey of teachers of higher educational institutions on the impact of new technologies on the teaching profession in order to identify problematic and positive aspects of the introduction of new educational technologies; - to analyze the best practices of introduction of new educational technologies in the leading universities of the world for the purpose of formation of the generalized algorithm of adaptation of new technologies to educational process and development of a pedagogical profession; - formulation of recommendations for ensuring high quality of online education and development of the pedagogical profession in the conditions of online learning. we note that new technologies will certainly improve the skills of teachers, but provided that the university creates the necessary working conditions.
New technologies and pedagogical profession: analysis of best practices (on the example of a group of universities)
Keywords: New technologies; Pedagogical profession; Best practices; Group of universities